2019
DOI: 10.7567/1347-4065/ab116c
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and scintillation properties of Ti-doped CaHfO3 crystals

Abstract: Ti-doped CaHfO 3 crystals were synthesized by the floating zone method equipped with xenon arc lamps, and the photoluminescence (PL) and scintillation properties are investigated. Ti-doped CaHfO 3 crystals emit strong blue photons under UV irradiation. The PL and scintillation signals are observed around 410 nm due to the charge transfer related to Ti 4+ . The PL and scintillation decay time constants are approximately 1 μs, which is relatively shorter than other Ti-doped materials. The scintillation light yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…The lifetime of the Ti-related emission appears to depend on the matrix crystal, but mostly previously reported lifetimes were of μs order. (14,16,20,27) Therefore, considering the emission wavelength and PL lifetime, we attributed the emissions at around 400 nm to charge-transfer (CT) transitions of Ti 4+ -O 2− . (27,28) CT emission generally follows a spin-and dipole-allowed absorption.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lifetime of the Ti-related emission appears to depend on the matrix crystal, but mostly previously reported lifetimes were of μs order. (14,16,20,27) Therefore, considering the emission wavelength and PL lifetime, we attributed the emissions at around 400 nm to charge-transfer (CT) transitions of Ti 4+ -O 2− . (27,28) CT emission generally follows a spin-and dipole-allowed absorption.…”
Section: Resultsmentioning
confidence: 99%
“…To grow these high-melting-point materials, a cruciblefree growth method such as the f loating zone (FZ) method can be used. (15) Our group has successfully synthesized some high-melting-point single cr ystals, for example, CaHfO 3 (16,17) and RE 2 Hf 2 O 7 (RE = La, Gd, and Lu) (14,18) doped with Ce and Ti. In particular, perovskite-type CaHfO 3 crystals exhibited the best scintillation properties among the Hf compounds we examined.…”
Section: Introductionmentioning
confidence: 99%
“…15 Calcium hafnate (CaHfO 3 , CH) is usually employed in insulating and optical applications because of its high breakdown strength, wide bandgap, and superior luminescence properties. [21][22][23][24] In the past decade, CH has also been incorporated in antiferroelectric and ferroelectric ceramics as a perovskite additive to improve energy storage performance. [25][26][27][28] In our latest study, 29 we revealed that the (0.67 − x)BiFeO 3 -0.33BaTiO 3 -xCaHfO 3 (BF-0.33BT-xCH) lead-free ceramics exhibited strong characteristics of relaxor ferroelectrics with high CH content.…”
Section: Introductionmentioning
confidence: 99%
“…(39)(40)(41)(42) In particular, the scintillation properties of perovskite-type hafnate single crystals have been investigated. (43,44) Ce:CaHfO 3 single crystals have been grown from a Ca-rich composition because CaO is volatilized at the melting point of CaHfO 3 . (45) The light yield of 3% Ce:CaHfO 3 is approximately 7800 photons/MeV, which is one of the highest values among the Hf-based oxide materials.…”
Section: Introductionmentioning
confidence: 99%